The Effect of Product Quality and Product Impact on Customer Satisfaction Purchase Decisions as Intervening Variables - Arwani, Agus; Andriyani, Putri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study is to determine the effect of product quality and product benefits on customer satisfaction through purchase. The research method uses a quantitative approach. The sample of 100 respondents. The data analysis is used in this study is path analysis. The product quality has a positive and significant effect on purchasing decisions with a significance value of 0,000 and a regression coefficient of 0,244, a significance value of 0,000 <0,05 (2) product benefit has a the significance value of 0,000 <0,05 (3) product quality has a positive and significant effect on consumer satisfaction with a significance of 0,002 and regression coefficient value of 0.140, (4) the benefit has a positive and significant effect on consumers satisfaction with a significance of 0.022 and a regression coefficient of 0.140, (5) purchasing decisions have a positive and significant effect on consumer satisfaction with a significance of 0,000 and a regression coefficient of 0.399,(6) product quality has a positive and significant effect on customer satisfaction through wit's purchasing decisions significance of 0,000 and a regression coefficient of 0.158(7)benefit has a positive and significant effect on customer satisfaction through purchasing decisions with significance of 0,000 and a regression coefficient of 0.210.